Implementation of Murottal Therapy to Reduce Preoperative Anxiety in Patients with Spinal Anesthesia - Erlena, Erlena Winda Lestari; Lintang Suryani, Roro; Bisma Yudha, Magenda (Java Nursing Journal, 2024)
Background: Preoperative anxiety is a common challenge that can negatively impact surgical outcomes and patient well-being. Physiological symptoms of anxiety, such as increased heart rate, blood pressure, and sweating, highlight the need for effective management strategies. Murottal therapy, which involves listening to Qur'anic recitations, offers a non-pharmacological method for anxiety reduction. Purpose: Evaluate murottal therapy’s effectiveness in reducing preoperative anxiety. Methods: A cohort of 30 patients scheduled for spinal anesthesia was recruited for this community service initiative. Anxiety levels were measured using the Visual Analog Scale for Anxiety (VAS-A) before and after the intervention. Participants underwent murottal therapy, which involved listening to Qur'anic recitations for a designated period. Pre- and post-therapy anxiety levels were compared to evaluate the effectiveness of the intervention. Findings: Prior to murottal therapy, 60% of participants exhibited severe anxiety, and 40% had moderate anxiety. Post-therapy results showed a significant improvement: 90% of participants reported moderate anxiety, 6.7% continued to experience severe anxiety, and 3.3% reported mild anxiety. Additionally, a pocket book detailing the murottal therapy procedure was developed as a resource for implementation. Conclusions: Murottal therapy significantly reduced anxiety levels among preoperative patients, demonstrating its potential as an effective, non-invasive approach to anxiety management in surgical settings.